Performance differences among skilled soccer players of different playing positions during vertical jumping and landing - Harry, J. R.; Barker, L. A.; James, C. R.; Dufek, J. S. (The Journal of Strength and Conditioning Research, 2018)
Both jumping and landing performance of skilled soccer players is diminished when task demands are increased. However, it is unclear if performance changes are specific to players of certain playing positions. Therefore, we assessed jumping and landing performance among skilled soccer players of different playing positions. Twenty-five National Collegiate Athletic Association (NCAA) Division 1 male soccer players (179.5 ± 7.8 cm, 75.5 ± 7.1 kg, 19.7 ± 1.2 years) performed maximum effort vertical jump landings (VJLs), whereas vertical ground reaction force (vGRF) data were obtained. Participants were stratified into goalkeeping (GK), defensive (DEF), midfield (MID), and attacking (ATT) group according to their primary playing position. One-way analyses of variance (a = 0.05) and effect sizes (ESs; large = 0.80) were used to compare differences among groups. The jumping phase variables evaluated were jump height, unloading and amortization vGRF magnitudes, eccentric rate of force development, and the reactive strength index. Landing phase variables included the peak vGRF magnitude, vGRF loading rate, vGRF attenuation rate, and landing time. No statistically significant differences were detected for any jumping or landing variable (p = 0.05). However, a number of large magnitude differences were detected during landing after ES calculations. Specifically, greater peak vGRF magnitudes were detected in DEF vs. both MID (ES = 1.08) and ATT (ES = 0.93), a greater vGRF loading rate occurred in DEF vs. MID (ES = 0.93), and a greater vGRF attenuation rate occurred in DEF vs. both MID (ES = 1.00) and AT (ES = 0.80). It is concluded that highly skilled soccer players possess position-specific abilities with respect to the landing phase of VJL. Skilled soccer players might experience enhanced training outcomes after VJL training regimens tailored to the specific demands of their primary playing position.